Literature Review: Water Quality of Public Bathing, Potential Health Problems and Water Borne Diseases on Visitors - Ummi Sholichatur Rachma; Retno Adriyani; Zida Husnina; Shofiyah Salma Farumi (JURNAL KESEHATAN LINGKUNGAN, 2021)
Introduction: Recreational Water Illnesses (RWIs) are diseases caused by pathogenic contaminants and harmful chemicals spread through direct contact with contaminated recreational water. Between 2011-2012, 1,700 cases caused by recreational water or Recreational Water Illness (RWIs) were recorded by the American Centers for Disease Control and Prevention (CDC). This study aims to analyzed the quality of water in public baths and the health problems based on current discussions of the previously published research. Discussion: This study was a literature review conducted by searching, selecting, synthesizing, and studying existing scientific articles and papers relevant to the topics discussed. These articles and papers were then objectively summarized and critically analyzed. There were 11 articles included (articles with appropriate topics published after 2010, original, systematic, and those located in Asia and Europe). This study found that the quality of water was an indicator key of health problems in public bathing. It caused various kinds of diseases such as disorders in the digestive system and respiratory as well as irritations in the skin, eye, and ear. Conclusion: This study concluded that water quality is crucial to several health problems complained about by public baths visitors. Future research is expected to use systematic literature review and meta-analysis methods to provide more solid scientific evidence based on the strong relationship between variables.Literature Review: Water Quality of Public Bathing, Potential Health Problems and Water Borne Diseases on Visitors